THE IMPACT OF REVERSE LOGISTICS, SUSTAINABLE PROCUREMENT, ETHICAL BRANDING, AND CONSUMER CONSCIOUSNESS ON MSME COMPETITIVENESS IN INDONESIA - Basneldi, Basneldi; Yusniar, Yusniar; Zukfikri, Agung (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study investigates the impact of reverse logistics, sustainable procurement, ethical branding, and consumer consciousness on the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS, data were collected from 210 MSMEs across various sectors. The results reveal that all three independent variables—reverse logistics, sustainable procurement, and ethical branding—significantly influence MSME competitiveness. Moreover, consumer consciousness not only has a direct positive effect on competitiveness but also moderates the relationships between each sustainable practice and competitiveness, strengthening their effects. These findings underscore the strategic importance of integrating sustainability into MSME operations and highlight the role of socially and environmentally aware consumers in amplifying business outcomes. The study contributes to the growing literature on sustainable business strategies in emerging economies and offers practical insights for MSMEs seeking to remain competitive in a value-driven market environment.